1998
DOI: 10.1074/jbc.273.2.784
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Adrenals Contain, in Addition to Ouabain, a Second Inhibitor of the Sodium Pump

Abstract: In the search for endogenous cardiac glycosides, two different inhibitors of the sodium pump have been isolated from bovine adrenals. Inhibitor A with a molecular mass of 600 Da and a UV maximum at 250 nm was purified from 16 kg of bovine adrenals. The pure substance (<1 ng) inhibited the sodium pump of human red blood cells with an affinity similar to that of ouabain, yet it cross-reacted with antibodies against the bufadienolide proscillaridin A but not against the cardenolide ouabain. Inhibitor A was slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
92
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(94 citation statements)
references
References 21 publications
1
92
0
1
Order By: Relevance
“…Ouabain is an endogenous steroid hormone that is present in mammalian tissues; it has been isolated from hypothalamus (39), adrenals (40), and human plasma (41). Evidence indicates that circulating levels of ouabain and ouabain-like factors are elevated during pregnancy and in newborn infants (13,32), thereby suggesting a developmental role for this signaling molecule.…”
Section: Discussionmentioning
confidence: 99%
“…Ouabain is an endogenous steroid hormone that is present in mammalian tissues; it has been isolated from hypothalamus (39), adrenals (40), and human plasma (41). Evidence indicates that circulating levels of ouabain and ouabain-like factors are elevated during pregnancy and in newborn infants (13,32), thereby suggesting a developmental role for this signaling molecule.…”
Section: Discussionmentioning
confidence: 99%
“…55 Mass spectrometry and nuclear magnetic resonance studies have indicated that mammalian endogenous ouabain is identical to plant-derived ouabain. 42,43,55 The adrenal cortex and hypothalamus are considered to be the sites of ouabain production in mammals. [55][56][57] Adrenocorticotropic hormone, angiotensin II, vasopressin, and phenylephrine stimulate the release of ouabain from the adrenal cortex in vitro.…”
Section: Subtypes Of Endogenous Cardiotonic Steroids Endogenous Cardementioning
confidence: 99%
“…Recently, Schneider et al (32) isolated another digitalislike substance, a proscillaridin A-like factor, from the bovine adrenal gland. They also report that OLI is present in the same tissue (32). Recently we found that ouabain was isolated from culture supernatant from PC12 cells in the presence of progesterone.…”
Section: Identification Of Endogenous Ouabainmentioning
confidence: 84%
“…Namely, our previous data suggested that the OLI in plasma is exclusively derived from the nervous tissue but not from adrenocortical tissue in rats (13). Schoner and his colleagues recently found a novel sodium pump inhibitor other than ouabain, which was found in the hypothalamus and the adrenal in rats and cows (32,35). Moreover, we (18), Leenen and his colleagues (36), and Yamada et al (37) reported the effect of ouabain on the central nervous system.…”
Section: The Site Of Endogenous Digitalis Productionmentioning
confidence: 92%